Manajemen Pengelolaan Terminal Penumpang Angkutan Darat Pada Terminal Untung Suropati Kota Pasuruan - Sulastri , Sulastri; Ardiono, Ahmad Rizki; Sugiarto, Rega Ardy (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The aim of this research is to identify the Land Transport Passenger Terminal Management at the Suropati Profit Bus Stop in Pasuruan City. This type of research is a qualitative approach and the type of research used is descriptive qualitative with basic and secondary sources of information. The number of informants in this research was 6 people. Information is obtained through monitoring, interviews (question and answer), and selection. The information analysis method used in this research is an interactive form of analysis, namely reducing information, providing information, and drawing conclusions. There is also a way to legalize information from research results, namely by triangulation results, namely base triangulation, method triangulation and duration triangulation. The research results show that the Management of Land Transport Passenger Terminal Management at the Suropati Profit Bus Stop in Pasuruan City is still very far from what is expected to be observed from the provision of education. Coordination, coverage and budgeting have not yet run optimally, resulting in problems at bus stops still not being resolved to date.